What Is “Telemedicine” and What Does It Mean for a Pediatric Surgeon? - Nalugo, Margaret; Craner, Domenic R.; Schwachter, Marc; Ponsky, Todd A. (European Journal of Pediatric Surgery, 2014)
Telemedicine is a broad term and has recently become a household term in the medical field. However, there are many interpretations as to what the term “telemedicine” means. There are many facets to telemedicine and here we describe all of the elements of telemedicine, a glossary of terms, and how they relate to pediatric surgery.
Keywords: telemedicine; pediatric surgery; telementoring; definition; telesurgery